Effect of stress management on blood pressure in mild primary hypertension. Issue 6883 (10th April 1993) - Johnston, D W; Gold, A; Kentish, J; Smith, D; Vallance, P; Shah, D; Leach, G; Robinson, B
Abstract : OBJECTIVE--To establish whether stress management had a larger effect than a control treatment on resting blood pressure, ambulatory blood pressure, and left ventricular mass. DESIGN--A 12 week baseline period of habituation to measurement of blood pressure was followed by randomisation to either stress management or mild exercise for six months and follow up six months later. SETTING--General practice, district general hospital, and medical school. PATIENTS--Of the 184 patients aged under 60 with mild primary hypertension who entered the baseline habituation period, 88 were excluded because they failed to meet the entry criteria or they withdrew from the study. The remaining 46 men and 50 women underwent treatment. INTERVENTIONS--10 clinical sessions and daily practice at home of either stress management based on relaxation or non-aerobic stretching exercises. Mildly stressful 15 minute interviews before and after treatment. MAIN OUTCOME MEASURES--Diastolic and systolic blood pressure in the clinic and during 12 hours of ambulatory recording, and left ventricular mass measured by echocardiography. RESULTS--The patients' blood pressure fell during habituation (systolic pressure from 152 mmHg to 140 mmHg, diastolic pressure from 98 to 93 mm Hg), but neither resting nor ambulatory blood pressure was changed by the treatments. Left ventricular mass was also unchanged. Blood pressure rose during the stressful interview, but this rise was reduced by stress management (systolic pressure rose by 7.4 mmHg before treatment and by 3.7 mmHg after treatment). CONCLUSION--Stress management of a type advocated for treating mild primary hypertension is ineffective in lowering blood pressure in patients who are well habituated to measuring blood pressure.